2019
DOI: 10.1111/mcn.12813
|View full text |Cite
|
Sign up to set email alerts
|

The perceptions and experiences of women with a body mass index ≥ 30 kg m2 who breastfeed: A meta‐synthesis

Abstract: Breastfeeding has copious health benefits for both mother and child, but rates of initiation and maintenance among women with a body mass index (BMI) ≥ 30 kg m 2 are low. Few interventions aiming to increase these rates have been successful, suggesting that breastfeeding behaviour in this group is not fully understood. Therefore, this review aimed to systematically identify and synthesise the qualitative literature that explored the perceptions and experiences of women with a BMI ≥ 30 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To improve breastfeeding, we need to focus on targeting theoretically sound and evidence-based factors using best-practice complex intervention design. The evidence supports the capability of women to engage in breastfeeding being positively underpinned by knowledge, women in particular recognizing the health benefits for optimal child nutrition and health outcomes ( Lyons, Currie & Peters, 2019 ). The importance of partners in supporting women to engage in breastfeeding is also acknowledged in previous work.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…To improve breastfeeding, we need to focus on targeting theoretically sound and evidence-based factors using best-practice complex intervention design. The evidence supports the capability of women to engage in breastfeeding being positively underpinned by knowledge, women in particular recognizing the health benefits for optimal child nutrition and health outcomes ( Lyons, Currie & Peters, 2019 ). The importance of partners in supporting women to engage in breastfeeding is also acknowledged in previous work.…”
Section: Discussionmentioning
confidence: 63%
“…Systematic reviews have highlighted that the barriers and enablers to breastfeeding for women with high BMIs were similar to other women, but that the extent of the experience may be more problematic for women with higher BMIs because of their weight status ( Chang et al, 2020 ; Lyons, Currie & Smith, 2019 ; Lyons, Currie & Peters, 2019 ). The physicality of breastfeeding and the stigma and social bias associated with high BMIs were pronounced findings in our results, which aligns with previous work ( Incollingo Rodriguez et al, 2020 ; Lyons, Currie & Smith, 2019 ). Our findings also demonstrated that, when participants with high BMIs were provided with the right support, in a way that is acceptable to them, they breastfeed for extended periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, this approach enabled synthesis of youth's SRH needs and preferences across individual papers with greater explanatory power than narrative or thematic approaches [49,50]. Its analytical nature and widespread use in non-ethnographies underscore its value [51][52][53][54].…”
Section: Data Synthesismentioning
confidence: 99%
“…Mothers with underweight as well as those with overweight/obesity experience higher rates of preterm birth, which itself is associated with delayed lactogenesis II, decreased expressed milk volumes, and early cessation, due to a variety of factors associated with preterm birth including early separation, maternal illness, and immature mammary glands [ 8 , 9 ]. Potential mechanisms underlying the relationship between overweight or obesity and lactation performance may include hormonal and metabolic alterations [ [10] , [11] , [12] , [13] ]. Specifically, prolactin and insulin may play a role.…”
Section: Introductionmentioning
confidence: 99%